The Effect of Think-Pair-Share Strategy on The Eighth Grade Students’ Descriptive Text Reading Comprehension Achievement at Junior High School - Agri Imandha Ruslen; Made Adi Andayani T.; Sudarsono Sudarsono (English Education Study Program, 2021)
This study aimed at finding whether there was an effect of Think-Pair-Share Strategy on the eighth grade students’ descriptive text reading comprehension achievement at Junior High School. The design used was quasi-experimental research with post-test only. The experimental group was given TPS strategy, while the control group was given the question and answer strategy as their teaching strategy. In the end, post-test was given to both groups and the data was analyzed using the independent sample t-test with 5% significant level by using SPSS software. The sig (2-tailed) was 0.010 which is less than 0.05 with 95% of significance level. The alternative hypothesis was accepted. Thus, there was a significant effect of TPS strategy on students’ reading comprehension.